PID self-tuning method based on deep belief network and improved firefly algorithm. (9th February 2021) - Yi, Lingzhi; Xu, Xiu; Tan, Mao; Zhang, Zongguang; Xiao, Weihong; Fan, Lv
In order to overcome the difficulty of tuning the proportion integration differentiation (PID) parameters, a PID parameter self-tuning method based on the firefly algorithm improved by Newton's law of universal gravitation (LOGFA) and deep belief network (DBN) is proposed. Compared with the FA, LOGFA cannot only maintain the evolutionary advantage of the original algorithm but also can effectively improve the accuracy and convergence ability of the algorithm. The advantage of DBN is to train each layer of neural network separately, which greatly improves the training efficiency and accuracy. The closed-loop PID speed control system of a three-phase asynchronous motor is used as the simulation object for PID parameter self-tuning. The proposed LOGFA-DBN is compared with other three algorithms. Simulation results show that the algorithm combining LOGFA and DBN can realise the off-line parameter tuning which is not subject to the controlled object, and speed up the parameter tuning.